UPAYA GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENINGKATKAN PRESTASI AKADEMIK PESERTA DIDIK PADA MATA PELAJARAN PAI DI SMP NEGERI 1 DUSUN SELATAN - Hidayatullah Hidayatullah (Al-Manba, 2026)
This study aims to find out about what are the efforts of Islamic Education and teachers to improve Academic Achievement of Students in the subjects of Islamic Education, as well as knowing what are the supporting and inhibiting factors and knowing the solutions to overcome these obstacles. This research uses qualitative method. The data collection techniques of this study are, observation, interviews, and documentation. Whereas the place of research is in SMP Negeri 1 Dusun Selatan , Ki Hajar Dewantara no 56 Buntok Desa/Kelurahan Hilir Sper. The results of this study are as follows: First, the efforts of Islamic Education Teachers to improve academic achievement of students, namely by conveying some motivation to students during teaching and learning activities, instilling discipline, varied learning methods, learning environments conducive, and become a good example. Second, the academic achievements of students in the subjects of Islamic Education in SMP Negeri 1 Dusun Selatan , Ki Hajar Dewantara no 56 Buntok Desa / Kelurahan Hilir Sper, namely in general it is good, with the average score on the subjects of Islamic Education and Pekerti having reached the criteria for completeness of drinking (KKM) which determined. Third, the supporting factors are a conducive learning environment, learning media, and learning methods. Fourth, the inhibiting factors are online games, learning media, and learning methods. Fifth, solutions to overcome these obstacles, conduct motivational training for students while teachers, namely teachers must master various methods, and teachers must master the material.